Development of an Enriched Lubi-Lubi (Ficus pseudopalma) Noodles - Fely A. Habla; Concepcion J. Cambaliza; Tarcela F. Detera; Mateo Luis G. Janer; Geraldine De Jesus (Philippine Association of Institutions for Research, Inc., 2012)
This research is focused on the development and acceptability of an enriched lubi-lubi (Ficus pseudopalma) noodle utilizing its puree as indigenous ingredients. Noodles were developed and enriched using lubi-lubi leaves. The level of acceptability was determined to find out the degree of acceptance of the noodles among consumers. Experimental method was used by extracting the puree of lubi-lubi leaves and used as flavor and packed/stored in polyethylene bag. Of the three trials conducted the enriched lubi-lubi noodles with ingredients of 250 g of Lubi-lubi leaves puree, 325 g APF, 10 g salt, 150g eggs and 2 g vegetable oil, 187.5 water was rated much acceptable. Based on acceptability level, trial 2 was rated as much acceptable as to taste and color and acceptable as to texture and odor. Sensory evaluation was done by the panelist using standard score sheets. Acceptability factors such as color, texture, flavor and odor were included among the choices. Results were obtained across prepared products, indicating the evident taste and aroma of lubi-lubi leaves through varied degree depending upon the quantity of puree used. The researchers observed correct mixing methods or techniques used flavorings and other materials that nicely blended with lubi-lubi puree as suggested by evaluators; the accepted ones were then standardized. The researchers concluded that lubi-lubi leaves are potential flavoring in the preparation of enriched lubi-lubi noodles and accepted among consumers.